Professional Netiquette and Its Pedagogical Integration in Business English Instruction for Future Digital Leaders - Nabilah, Nada (Digital Business Progress, 2025)
This study examines the role of professional netiquette in Business English instruction within a digitalized learning environment for management students. As communication in modern business increasingly relies on email, messaging platforms, video-conferencing, and Learning Management Systems, digital etiquette has become essential for maintaining professionalism and communicative effectiveness. Using a descriptive qualitative design, this study analyzed three units of Speaking and Business English instructional materials from the Management Department, focusing on learning objectives, instructional activities, and assessment tasks. Additional documents such as syllabi, worksheets, and rubrics were included to strengthen the analysis. The findings show that students possess only a moderate awareness of netiquette, with inconsistent performance across email writing, instant messaging, virtual meetings, and LMS interactions. Students, however, perceive netiquette as highly relevant to their future roles in digital business, particularly in areas related to credibility, remote teamwork, and customer communication. The study identifies several pedagogical strategies for integrating netiquette into Business English instruction, including explicit teaching of digital etiquette principles, authentic digital communication tasks, improved feedback mechanisms, reflective learning activities, and curriculum alignment. These findings emphasize the need for curriculum innovation that prepares students to communicate ethically, professionally, and effectively in digital business environments.